Liberalizing financial services trade in Africa: Going regional and multilateral - Marion Jansen; Yannick Vennes (World Trade Organization (WTO), 2006)
This paper analyses the possible gains from regional and multilateral liberalization of financial services trade for African countries taking into account the implications of such liberalization for financial regulation and capital account liberalization. It also describes existing efforts to integrate financial markets within four African regions (WAEMU, CEMAC, SADC and COMESA) and discusses the existing GATS commitments of the relevant countries with respect to financial services. Although the regions differ significantly, there is scope for further regional integration in all of them. Significant scope also exists for further multilateral liberalization of financial services, in particular with respect to Mode3.
Keywords: F13; F15; G21; G38; 330; regional integration; WTO; financial services trade; Africa